ONLINE-OFFLINE TEACHING: EXPLORING SOME ASPECTS AND PROMOTING DEVELOPMENT (Нововведения Cовременного Научного Развития в Эпоху Глобализации: Проблемы и Решения, 2023)
This thesis article delves into the distinct characteristics and developmental aspects of online-offline teaching in the field of education. With the advent of technology, traditional offline teaching approaches have evolved to incorporate online components, resulting in a blended instructional approach. This article investigates the unique aspects of online-offline teaching, explores its benefits and challenges, and presents strategies for its effective implementation. By understanding the intricacies and potential of this hybrid teaching model, educators can optimize student learning experiences and foster educational development in the digital age.